They Called You Dambudzo : a Memoir - Veit-Wild, Flora, 1947- (James Curry, 2022)
Compelling memoir of Flora Veit-Wild and her relationship with the Zimbabwean novelist, poet, playwright, and essayist Dambudzo Marechera, one of Africa's most innovative and subversive writers and a significant voice in contemporary world literature.